Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1172/jci108378
|View full text |Cite
|
Sign up to set email alerts
|

An anomaly of insulin removal in perfused livers of obese-hyperglycemic (ob/ob) mice.

Abstract: A B S T R A C T Obese-hyperglycemic (ob/ob) mice have the interesting feature of being hyperinsulinemic, thus having some characteristics in common with human maturity-onset diabetics. As the cause of hyperinsulinemia in these mice is not established, and as the liver is known to play a role in determining the amount of hormone that reaches the periphery, it was hypothesized that an anomaly in the hepatic handling of insulin might prevail in obese-hyperglycemic mice. Immunoreactive insulin was therefore measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 21 publications
(24 reference statements)
4
25
0
Order By: Relevance
“…In these studies, following glucose, hepatic plasma flow increased approximately twofold from a mean of 340 to 688 ml/min; most of this increment can reasonably be attributed to portal vein increases. Although this question has not been addressed directly in vivo, Karakash et al (26) showed that insulin extraction by perfused rat liver remained constant despite doubling of the perfusion rate. On the other hand, Misbin et al (21), using a similar system, showed that hepatic insulin clearance depended in part on the portal flow rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, following glucose, hepatic plasma flow increased approximately twofold from a mean of 340 to 688 ml/min; most of this increment can reasonably be attributed to portal vein increases. Although this question has not been addressed directly in vivo, Karakash et al (26) showed that insulin extraction by perfused rat liver remained constant despite doubling of the perfusion rate. On the other hand, Misbin et al (21), using a similar system, showed that hepatic insulin clearance depended in part on the portal flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…end sampling catheters were placed in the portal and hepatic veins of seven mongrel dogs (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) kg; mean weight 22±1.6 kg) according to the methods described by Cherrington et al (10). The portal vein catheter was introduced via the spleen and secured in the portal vein just before its bifurcation into right and left branches in the porta hepatis.…”
Section: Methodsmentioning
confidence: 99%
“…The number of insulin receptors on the membrane may be an important determining factor in the rate of insulin degradation by intact tissues. Indeed, in states of hyperinsulinism, where a decreased number of receptors is found, insulin degradation by the liver is decreased despite an increase in total degrading activity found intracellularly (38). The situation in vivo, however, is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuations in receptor concentration or receptor affinity, as has been demonstrated under numerous circumstances in vivo, will have a great effect on how closely the areas under the curves reflect secretion. For example, Karakash et al (50) found that in the obese-hyperglycemic mouse (where presumably receptor concentrations are reduced to 1/3 of normal) the uptake of insulin across the liver was reduced substantially, presumably reflecting the decreasedl binding to receptor. Thus, identical curves of plasma hormone versus time will indicate identical secretory rates only when receptor concentration and receptor affinity are unchanged.…”
Section: Discussionmentioning
confidence: 99%